RANCANG BANGUN APLIKASI KARTU MENUJU SEHAT (e-KMS) PADA PLATFORM ANDROID - Kurnia Muludi; Noni Kurniasih; Aristoteles Aristoteles; Muhammad Iqbal (Lambung Mangkurat University, 2020)
Toddler Growth Chart held by parents is a book that consists of a toddler's growth history which holds by Maternal and Child Health Services (Posyandu) officer. Growth Chartbook still uses traditional ways, written by hands to records all of the toddler's growth. Posyandu reports that sent to the Public Health Center (Puskesmas) every month still proceeds with a spreadsheet, and it makes Posyandu officers felt the difficulty of processing the data, like record, search, and store the data. e-KMS Apps can help Posyandu officers for easy recording and searching , and tracing data history. It also helps Posyandu officers to make Posyandu reports easily. This app helps toddler’s parents to control their toddler’s growth and make the parents feel easy about how to take care of the toddlers. This application is equipped with features of calculating nutrition status and presenting toddler nutrition status data in the graph based on WHO (World Health Organization) standards in 2006, Posyandu activities, calculation of nutritional status for parents of children under five to be able for knowing the nutritional status of toddlers anywhere and at any time without waiting for the Posyandu schedule. It also provides tips and tricks for caring for toddlers to inform parents how to care for toddlers, and manages Posyandu reports every month to control the condition of toddlers.Keywords: Android, Growth Chart, Nutritional Status, Child Health Service.Kartu Menuju Sehat (KMS) merupakan kartu yang berisi data kesehatan bayi secara berkala yang dipegang oleh orang tua. Pembukuan data ini mempersulit kader posyandu dalam pencatatan, pencarian dan penyimpanan data Balita. Selama ini Laporan Posyandu dikumpulkan ke Puskesmas pada tiap bulan dan diolah menggunakan spreadsheet. Tidak jarang cara ini sering mengakibatkan proses pengiputan mengalami kesalahan. Aplikasi mobile KMS (e-KMS) dapat mempermudah kader Posyandu dalam proses di atas sekaligus dapat mengelola laporan Posyandu dengan lebih mudah. Aplikasi ini juga mempermudah orang tua dalam memonitor kondisi perkembangan balita dan mengetahui bagaimana cara merawat balita. Fitur-fitur lain yang disediakan pada e-KMS diantaranya adalah perhitungan status gizi dan penyajiannya dalam bentuk grafik menggunakan standar WHO (World Health Organization), dan informasi kegiatan Posyandu. Tips dan trik merawat balita disediakan juga untuk memberi membantu pada orang tua cara merawat Balita. Kata Kunci: Android, KMS (Kartu Menuju Sehat), Posyandu, status gizi balita.